2020
DOI: 10.3390/jpm10030112
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Characterization of Immune Infiltrate in Tumor Microenvironment of Glioblastoma

Abstract: Background: Glioblastoma (GBM) is the most common primary malignant brain cancer in adults, with very limited therapeutic options. It is characterized by a severe immunosuppressive milieu mostly triggered by suppressive CD163+ tumor-associated macrophages (TAMs). The efficacy of immune checkpoint inhibitor interventions aimed at rescuing anti-tumor immunity has not been proved to date. Thus, it is critically important to investigate the immunomodulatory mechanisms acting within the GBM microenvironment for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 49 publications
1
18
0
Order By: Relevance
“…The glutamine-addicted GBM mesenchymal cells arise from neoplastic microglia/macrophages (118,119). A recent study showed that expression of the macrophage/microglial marker, CD163, was lower in an IDH1mutant GBM than in IDH1 wild-type GBM (120). CD163 is a biomarker for glutamine-dependent neoplastic macrophages in tumor tissue (119,121).…”
Section: Discussionmentioning
confidence: 99%
“…The glutamine-addicted GBM mesenchymal cells arise from neoplastic microglia/macrophages (118,119). A recent study showed that expression of the macrophage/microglial marker, CD163, was lower in an IDH1mutant GBM than in IDH1 wild-type GBM (120). CD163 is a biomarker for glutamine-dependent neoplastic macrophages in tumor tissue (119,121).…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that there are different preferential distributions and functions of GAMs in different locations, as well as in different GBM subtypes. In an immunohistochemical analysis of a panel of immune biomarkers within the GBM microenvironment, the CD163 + pro-tumoral macrophages appeared to be the most common cell type in both the peritumoral area (PTA) and the tumor core (TC) [ 14 ]. Similarly, another study proved that in central tumor areas and around vessels in the infiltration zone there were more CD68+ GAMs in slow-growing tumors.…”
Section: Glioblastoma Associated Macrophages/microgliamentioning
confidence: 99%
“…The clinical benefit of these therapies administrated alone or in combination is already well established in several cancer types (melanoma, lung cancer, renal cell carcinoma) [ 1 , 2 , 3 ]. In other tumors with limited therapeutic options such as glioblastoma, research efforts are focused on possible combination therapies on the tumor microenvironment [ 4 ]. These treatments may confer different benefits if combined with standard therapies [ 5 ].…”
Section: Introductionmentioning
confidence: 99%